Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1103/physreva.90.053603
|View full text |Cite
|
Sign up to set email alerts
|

Coherence lengths in attractively interacting Fermi gases with spin-orbit coupling

Abstract: Extensive research has been lavished on the effects of spin-orbit couplings (SOCs) in attractively interacting Fermi systems in both neutral cold-atom systems and condensed-matter systems. Recently, it was suggested that a SOC drives a class of BCS to Bose-Einstein condensate (BEC) crossover that is different from the conventional one without a SOC. Here, we explore what are the most relevant physical quantities to describe such a BCS to BEC crossover and their experimental detections. We extend the concepts o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
0
9
1
Order By: Relevance
“…ωmin denotes the lower edge of inter-band particle-hold continuum, which is taken as the unit in Fig.8(d never a ground state in the former system, but it maybe a ground state in the latter. As shown in the Sec.II, the [SU (2) spin × SO (3) orbit ] D symmetry [13,17] dictates that the dynamical 4 × 4 density-spin susceptibility Eqn.14 can be split into two 2 × 2 subspaces: i) n − L subspace formed by the density and the longitudinal spin mode ii) T 1 − T 2 subspace formed by the two transverse modes. This exact decomposition simplifies the following analytical and numerical calculations considerably.…”
Section: Summaries and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ωmin denotes the lower edge of inter-band particle-hold continuum, which is taken as the unit in Fig.8(d never a ground state in the former system, but it maybe a ground state in the latter. As shown in the Sec.II, the [SU (2) spin × SO (3) orbit ] D symmetry [13,17] dictates that the dynamical 4 × 4 density-spin susceptibility Eqn.14 can be split into two 2 × 2 subspaces: i) n − L subspace formed by the density and the longitudinal spin mode ii) T 1 − T 2 subspace formed by the two transverse modes. This exact decomposition simplifies the following analytical and numerical calculations considerably.…”
Section: Summaries and Discussionmentioning
confidence: 99%
“…So the 3d isotropic (Weyl) SOC is expected to be implemented in very near future experiments. So far, there were extensive theoretical investigations on various effects of SOC on the pairing physics of attractively interacting Fermi gases [12,13]. However, there are still relatively few works in the repulsive side.…”
Section: Introductionmentioning
confidence: 99%
“…Spectra for ω 1 (0) and ω 2 (0) in the BEC limit (1/k F a s = +4.0) varying the hybridization V /E F for α = 0.5. In the inset the behavior of ω 2 (0) is shown for (15) where ω 2 (0) also depends of and μ…”
mentioning
confidence: 97%
“…The Superconducting-Insulator transition (SIT) observed in these disordered systems as the indium oxide (InO) compound [14] are related to the Cooper-pair localization. Recently Yi-Xiang et al [15] have studied the effects of spin-orbit couplings (SOC) in attractively interacting Fermi systems such as the cold atom systems and usual condensed matter systems. The authors have investigated the effects of SOC on the BCS-BEC crossover.…”
mentioning
confidence: 99%
“…In the presence of the SOC, it has been suggested that a BEC can be realized even at a fixed weak interaction where very strong SOC can lead to the formation of the bosonic bound state called rashbon [30][31][32]. The BCS-BEC crossover in spin-orbit-coupled Fermi gases has been studied with various settings of SOC, interaction, and dimensionality in the mean-field theory [33][34][35][36][37][38][39][40][41][42][43], also in the beyond-mean-field approaches for three [44][45][46][47][48] and two * dongheekim@gist.ac.kr dimensions [49][50][51][52], and very recently by using the quantum Monte Carlo (QMC) method for the ground state in two dimensions [53].…”
Section: Introductionmentioning
confidence: 99%